The Activities Faced by Lecturers` Receptive Skills in Covid-19 Pandemic at STKIP-PGRI Lubuklinggau - Fitra Rahmadanti Fitra; Ayu Oktaviani; Dewi Syafitri (Jurnal Riset Madrasah Ibtidaiyah, 2022)
Nowadays, the education situation still in a struggle stage. This is because of the situation of Covid-19 pandemic. This situation made the govermen issued some policy. It made the teaching and learning process in this time have to implement Blended learning. This methos was a new for some lecturer one of them were the lecturers in STKIP-PGRI Lubuklinggau. They still face some challenges in applied this method because there was no a significant or fixed guidline in teaching process both in online or offline classroom. Based on the fenomena, this research aims to carry out the teaching activities done by lecturers` receptive skills in the Covid-19 period at STKIP-PGRI Lubuklinggau in implementing Blended Learning. The research informants were the lecturers` receptive skills that consisted of 2 reading skill lecturers and 1 listening skill lecturer. They taught with Blended Learning in the even semester of the academic year 2020/2021. This research was descriptive qualitative. The research instruments were questionnaires and interview. The instruments adopted from the activity theory by Meliawati, Nitiasih and Budasi (2014). The technique of data analysis were reduction, display and conclusion. The results showed the activities carried out by lecturers during teaching with Blended Learning consist of 3 parts: Pre-activity, Whilst-activity and Post-activity where each part consists of two different activities between online classes and offline classes.